Clinical-grade autonomous cytopathology through whole-slide edge tomography - Nao Nitta; Yuko Sugiyama; Takeaki Sugimura; Takahiko Ito; Koichi Ikebata; Hitoshi Abe; Shuhei Ishii; Hiroyuki Kanao; Nagisa Hosoya; Raihan Ull Islam; Aditya Jain; Meisam Hasani; et al. (Nature, 2026)
Abstract Cytopathology, often abbreviated as cytology, has a central role in the early detection of cancer, such as cervical, lung and bladder cancers, owing to its speed, simplicity and minimally invasive nature 1–9 . However, its effectiveness is limited by variability in diagnostic accuracy stemming from subjective visual interpretation 10–21 . Although many artificial intelligence (AI)-powered systems have been proposed to improve consistency 22–26 , none have achieved fully autonomous, clinical-grade performance. Existing approaches serve as assistive tools and still rely on human oversight for interpretation and decision-making 22–26 . Here we present a clinical-grade autonomous cytopathology pipeline that combines high-resolution, real-time optical whole-slide tomography with edge computing to deliver end-to-end automation. The system achieves practical performance in imaging speed, quality and data volume, with localized data compression enabling streamlined storage and accelerated AI-driven analysis. In addition to supporting cell-level classification, the platform enables flow cytometry-like, population-wide morphological profiling for comprehensive interpretation of cellular distributions and patterns. A vision transformer achieved area under the receiver operating characteristic (ROC) curve (AUC) values exceeding 0.99 at the single-cell level for detecting low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial lesions (HSILs) and adenocarcinoma. In a multicentre evaluation of 1,124 cervical liquid-based cytology samples across four centres, the AI model achieved slide-level AUC values of 0.86–0.91 for LSIL + and 0.89–0.97 for HSIL + , with LSIL counts correlating strongly with human papillomavirus positivity and HSIL counts scaling with diagnostic severity. The system enables autonomous triage cytology, offering a foundation for routine, scalable and objective diagnostics.